Pbat composite material and preparation method and application thereof

CN120399412BActive Publication Date: 2026-10-27KINGFA SCI & TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410136530.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2026-10-27
Estimated Expiration
2044-01-31

Smart Images

  • Figure BDA0004691454870000011
    Figure BDA0004691454870000011
  • Figure BDA0004691454870000021
    Figure BDA0004691454870000021
  • Figure BDA0004691454870000041
    Figure BDA0004691454870000041
Patent Text Reader

Abstract

The present application relates to a kind of PBAT composite material and its preparation method and application.The PBAT composite material includes the following weight parts of component: 3-20 parts of polylactic acid, 40-80 parts of PBAT resin, 0.1-10 parts of polyester, 10-40 parts of filler.The content of terephthalic acid derivative unit in PBAT resin is regulated in the present application, and polylactic acid, filler and a certain amount of specific terephthalic acid derivative unit content polyester are added, and the PBAT composite material keeps good degradation performance, while good film blowing opening performance and printing performance are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer material modification technology, and more specifically, to a PBAT composite material, its preparation method, and its application. Background Technology

[0002] With the accelerated elimination of outdated production capacity and the continuous advancement of industrial restructuring, many businesses in the environmental protection industry are penetrating from end-of-pipe treatment to various production stages. In the film industry, fully biodegradable films have received widespread attention from various countries and are expected to solve the problem of white pollution.

[0003] PBAT, as a material with excellent biodegradability, combines the characteristics of PBA and PBT, exhibiting good ductility and elongation at break, as well as good heat resistance and impact resistance. However, PBAT has poor processability and poor opening properties during blown film production, which hinders its large-scale promotion and use.

[0004] In existing technologies, opening agents (such as erucamide, oleamide, etc.) are usually added to improve the opening performance of PBAT materials. However, opening agents are often small molecules that can easily migrate to the surface of the product, resulting in poor ink adhesion.

[0005] Patent CN 103709687A improves the opening performance of the film material by adding Ciba's anti-adhesion agent SR100 to PBAT, but it does not focus on the printability of the material.

[0006] Therefore, it is necessary to develop technologies to solve the problem that the blown film opening performance and printing performance of current PBAT materials cannot be simultaneously achieved. Summary of the Invention

[0007] The primary objective of this invention is to overcome the problem that the blown film opening performance and printing performance of PBAT materials in the current technology cannot be simultaneously achieved, and to provide a PBAT composite material.

[0008] A further object of the present invention is to provide a method for preparing the above-mentioned PBAT composite material.

[0009] A further object of the present invention is to provide the application of the above-mentioned PBAT composite material in the preparation of thin film products.

[0010] The above-mentioned objective of the present invention is achieved through the following technical solution:

[0011] A PBAT composite material comprises the following components in parts by weight:

[0012]

[0013]

[0014] In the PBAT resin, the proportion of terephthalic acid-derived units relative to all dicarboxylic acid-derived units is 44-52 mol%, specifically 44 mol%, 45 mol%, 46 mol%, 48 mol%, 50 mol%, or 52 mol%.

[0015] In the polyester, the dicarboxylic acid derivative unit is derived from terephthalic acid and C. 4~10 The PBAT resin or polyester contains aliphatic dicarboxylic acids, and the terephthalic acid-derived unit accounts for 55–80 mol% of all dicarboxylic acid-derived units (specifically, 55 mol%, 58 mol%, 60 mol%, 62 mol%, 65 mol%, 68 mol%, 70 mol%, 72 mol%, 75 mol%, 78 mol%, or 80 mol%), with the diol-derived unit derived from butanediol. In this invention, the percentage of terephthalic acid-derived units in the PBAT resin or polyester relative to all dicarboxylic acid-derived units can be determined by NMR.

[0016] The inventors of this invention discovered through research that adding polylactic acid to PBAT composite materials can improve the crystallinity of the material to a certain extent and thus improve the blown film opening performance of the material.

[0017] Further research by the inventors revealed that by adding polylactic acid and then adjusting the content of phthalic acid-derived units in the PBAT resin, as well as adding polyester with a specific content of terephthalic acid-derived units, the opening performance of the PBAT composite material can be significantly improved without the addition of opening agents and lubricants. Furthermore, it exhibits good ink adhesion and excellent printability. The reason for this is likely that adjusting the content of terephthalic acid-derived units in the PBAT resin, along with the amount of polyester and the content of terephthalic acid-derived units, can more effectively control the material's hardness, melting point, and crystallinity, thereby effectively improving the material's opening performance while maintaining printability.

[0018] If the terephthalic acid-derived unit content of PBAT resin is too low, or if polyester with a specific terephthalic acid-derived unit content is not added, the opening properties of PBAT composites cannot be significantly improved. If the terephthalic acid-derived unit content of PBAT resin is too high, or if too much polyester with a specific terephthalic acid-derived unit content is added, it will negatively impact the degradation properties of PBAT composites, failing to meet their conventional application requirements.

[0019] The addition of fillers also helps to improve the opening performance and printability of PBAT composite materials.

[0020] This invention regulates the content of terephthalic acid derivative units in PBAT resin and adds polylactic acid, fillers, and a certain amount of polyester with specific terephthalic acid derivative unit content to obtain a PBAT composite material that maintains good degradation performance while also taking into account good blown film opening performance and printing performance.

[0021] Optionally, the melt flow rate of the polylactic acid is 1–10 g / 10 min.

[0022] In this invention, the melt mass flow rate of polylactic acid was measured according to ISO 1133 using 2.16 kg weight and at a temperature of 190°C.

[0023] Preferably, the polylactic acid has a melt flow rate of 4 to 4.5 g / 10 min. Using polylactic acid with this melt flow rate results in better retention of the degradation performance of the PBAT composite material.

[0024] Preferably, the residual monophenol content of the polylactic acid is ≤0.5wt%.

[0025] Optionally, the intrinsic viscosity of the PBAT resin is 0.9 dL / g to 1.5 dL / g.

[0026] In this invention, the intrinsic viscosity of PBAT resin is determined according to DIN 53728, Part 3 of January 3, 1985, and the solvent used includes a mixture of phenol and dichlorobenzene in a weight ratio of 50:50; the test temperature is 25°C.

[0027] Preferably, the intrinsic viscosity of the PBAT resin is 1.3 dL / g to 1.5 dL / g. Within this range, the PBAT composite material has better printability.

[0028] Preferably, in the PBAT resin, the proportion of terephthalic acid derivative units relative to all dicarboxylic acid derivative units is 48-52 mol%, and within this range, the PBAT composite material has better printability.

[0029] Optionally, the intrinsic viscosity of the polyester is 1.3 dL / g to 1.5 dL / g.

[0030] In this invention, the intrinsic viscosity of the polyester is determined according to DIN 53728, Part 3 of January 3, 1985, and the solvent used includes a mixture of phenol and dichlorobenzene in a weight ratio of 50:50; the test temperature is 25°C.

[0031] Preferably, in the polyester, the proportion of terephthalic acid-derived units relative to all dicarboxylic acid-derived units is 65-80 mol%. Within this range, the blown film opening performance and printability of the obtained PBAT composite material are better.

[0032] Optionally, the polyester is at least one of polybutylene terephthalate, polybutylene adipate, polybutylene azelaate, or polybutylene sebacate.

[0033] Preferably, the polyester is butylene sebacate terephthalate (PBAT), and the PBAT composite material obtained by using butylene sebacate terephthalate has better printability.

[0034] Optionally, the filler is at least one of calcium carbonate, talc, kaolin, mica powder, or montmorillonite.

[0035] Optionally, the D50 particle size of the filler is ≤10μm.

[0036] In this invention, the D50 particle size of the filler can be measured according to GB / T 19077.1 "Particle size analysis by laser diffraction".

[0037] Optionally, the PBAT composite material further includes 0.1 to 2 parts of other additives.

[0038] Optionally, the other additives are at least one of antioxidants, stabilizers, antistatic agents, antifogging agents, UV absorbers, and UV stabilizers.

[0039] Typically, the amounts of other additives are as follows: antioxidant 0.01 to 0.3 parts by weight, stabilizer 0.05 to 1 part by weight, antistatic agent 0.01 to 0.5 parts by weight, UV absorber 0.05 to 2 parts by weight, and UV stabilizer 0.1 to 3 parts by weight.

[0040] Optionally, the antioxidant is at least one of antioxidant 1010 or antioxidant 168;

[0041] Optionally, the stabilizer is at least one of tribasic lead sulfate, dibasic lead stearate, lead stearate, calcium stearate, zinc stearate, or magnesium stearate;

[0042] Optionally, the antistatic agent is at least one of ethoxylated alkylamine, ethoxylated alkyl acid amine, or glycerol stearate;

[0043] Optionally, the antifogging agent is at least one of glycerol ester, polyglycerol ester, sorbitol ester, ethoxylated derivative, ethoxylated nonylphenol, or ethoxylated alcohol;

[0044] Optionally, the UV absorber is at least one of phenyl benzoate, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, or 2-hydroxy-4-n-octyloxybenzophenone.

[0045] Optionally, the UV stabilizer is at least one of bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate or 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-(2,4-dimethylphenyl)-2H-benzotriazine-4-one.

[0046] Preferably, the PBAT composite material comprises the following components in parts by weight:

[0047]

[0048] The preparation method of the above-mentioned PBAT composite material includes the following steps: mixing the components, melt extruding, and granulating to obtain the PBAT composite material.

[0049] The application of the above-mentioned PBAT composite material in the preparation of thin film products is also within the scope of protection of this invention.

[0050] Preferably, the film product is a shopping bag, garbage bag, or packaging bag.

[0051] Compared with the prior art, the beneficial effects of the present invention are:

[0052] This invention regulates the content of terephthalic acid-derived units in PBAT resin and adds polylactic acid, fillers, and a certain amount of polyester with specific terephthalic acid-derived unit content to obtain PBAT composite materials that maintain good degradation performance while also taking into account good blown film opening performance and printing performance. Detailed Implementation

[0053] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0054] The reagents used in the various embodiments and comparative examples of this invention are described below:

[0055] Polylactic acid 1#: purchased from Nature Works, grade: PLA 4044D, melt index: 4.5 g / 10 min;

[0056] Polylactic acid 2#: purchased from Nature Works, PLA 3001D, melt index is 10g / 10min;

[0057] Polylactic acid 3#: purchased from Nature Works, PLA 752-27, melt index 4.0 g / 10 min;

[0058] The residual monomer content of polylactic acid in this invention was tested as follows:

[0059] 1. Preparation of standard solutions

[0060] (1) Weigh 100±10 mg of pentamethylbenzene, prepare 100 mL of dichloromethane solution, and shake well. Record this as the internal standard solution;

[0061] (2) Weigh 100±10mg of L-lactide standard, prepare 100mL of dichloromethane solution, shake well, and record it as standard solution;

[0062] (3) Take volumes of 1.0, 2.0, 5.0, 10.0, and 20.0 mL from the standard solution and transfer them to 25 mL volumetric flasks. Add 4.0 mL of internal standard solution to each flask, fill with n-hexane, and mix well at a constant temperature. These are denoted as calibration standard solutions.

[0063] 2. Sample Testing

[0064] (1) Weigh 200±20mg of polylactic acid sample (W) into a 20ml glass vial and add 4.0mL of internal standard solution. Dissolve the sample at room temperature, stirring to aid dissolution. After the sample is completely dissolved, slowly add 10mL of n-hexane to the inner wall of the flask, seal the vial tightly, and then shake vigorously for 5-10 seconds. Let the sample stand for 10 minutes.

[0065] (2) After filtration with a membrane filter, transfer the sample into a dedicated gas chromatography vial and test it according to the above gas chromatography analysis conditions. Each sample solution should be injected at least 3 times.

[0066] 3. Calculation of residual polylactic acid monomer content

[0067] Calculate the area ratio (ARS) of lactide and pentamethylbenzene in the injected sample, and read the corresponding content ratio (CRS) from the calibration curve.

[0068] The lactide content of the sample during each GC run was calculated using the following method:

[0069]

[0070] CRS: The percentage of content read from the calibration curve;

[0071] ISS: The mass of pentamethylbenzene present in 100 mL of the internal standard solution used for sample determination [mg / 100 mL];

[0072] W: Mass of PLA sample taken [mg].

[0073] PBAT Resin #1: Self-made, preparation method as follows:

[0074] 1) Terephthalic acid and 1,4-butanediol were added to the esterification reactor at a molar ratio of 1:1.2, and 1% of the total mass of the raw materials was added as catalyst n-butyl titanate. The reaction was carried out at a temperature of 240℃ and a pressure of 40KPa for 2.5h to obtain esterified product A1.

[0075] 2) Adipic acid and 1,4-butanediol were added to the esterification reactor in a molar ratio of 1:1.3 and reacted for 2.5 h at a temperature of 200℃ and a pressure of 40 kPa to obtain esterified product A2;

[0076] 3) Two esters, A1 and A2, were continuously fed into a mixer and mixed at a mass flow ratio of 1:1. The reaction was carried out at 240℃ and 4 kPa for 2.5 h to obtain a prepolymer. Polymerization was then continued at 200℃ and 120 Pa for another 2.5 h to obtain PBAT resin #1. The T content (the percentage of terephthalic acid-derived units relative to all dicarboxylic acid-derived units) was 48 mol%; the intrinsic viscosity was 1.36 dL / g.

[0077] The T content can be determined by NMR. The specific process is as follows: test the 1H NMR spectrum of the sample and calculate the peak area of ​​the corresponding peak. Measure the molar fraction of polybutylene terephthalate in the sample. Taking PBAT resin #1 as an example, the calculation method is as follows:

[0078] T = A 8.09 / (A 8.09 +A 2.33 )

[0079] Where T represents the molar fraction of polybutylene terephthalate (PBAT), which is the molar percentage of terephthalic acid-derived units relative to all dicarboxylic acid-derived units.

[0080] A 8.09 This represents the peak area at 8.09 in the NMR spectrum;

[0081] A 2.33 This represents the peak area at 2.33 in the NMR spectrum.

[0082] The measurement process for the T content of other PBAT resins or polyesters is similar.

[0083] PBAT Resin 2#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference being: in step 3), the T content is adjusted by adjusting the mass flow ratio of A1 and A2. Finally, PBAT Resin 2# is obtained, with a T content of 45 mol% and an intrinsic viscosity of 1.35 dL / g.

[0084] PBAT Resin 3#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference being that in step 3), the T content is adjusted by adjusting the mass flow ratio of A1 and A2. Finally, PBAT Resin 3# was obtained with a T content of 52 mol% and an intrinsic viscosity of 1.36 dL / g.

[0085] PBAT Resin 4#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference being that in step 3), the T content is adjusted by adjusting the mass flow rate ratio of A1 and A2. Finally, PBAT Resin 4# is obtained with a T content of 50 mol% and an intrinsic viscosity of 1.37 dL / g.

[0086] PBAT Resin 5#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference is: in step 3), after obtaining the prepolymer, it is continued to polymerize for 1.5h at a temperature of 200℃ and a pressure of 120Pa. Finally, PBAT Resin 5# is obtained, with a T content of 48mol% and an intrinsic viscosity of 0.9dL / g.

[0087] PBAT Resin 6#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference is: in step 3), after obtaining the prepolymer, it is continued to polymerize for 3.5h at a temperature of 200℃ and a pressure of 120Pa. Finally, PBAT Resin 6# is obtained, with a T content of 48mol% and an intrinsic viscosity of 1.5dL / g.

[0088] PBAT Resin 7#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference being: in step 3), the T content is adjusted by adjusting the mass flow ratio of A1 and A2. Finally, PBAT Resin 7# is obtained, with a T content of 42 mol% and an intrinsic viscosity of 1.36 dL / g.

[0089] PBAT Resin 8#: Self-made, the preparation method is basically the same as PBAT Resin 1#, the difference being: in step 3), the T content is adjusted by adjusting the mass flow ratio of A1 and A2. Finally, PBAT Resin 8# was obtained with a T content of 53.5 mol% and an intrinsic viscosity of 1.36 dL / g.

[0090] Polyester 1#: Self-made, preparation method is as follows:

[0091] 1) Terephthalic acid and 1,4-butanediol were added to the esterification reactor in a molar ratio of 1:1.2, and 1% of the total mass of the raw materials was added as catalyst n-butyl titanate. The reaction was carried out at a temperature of 240℃ and a pressure of 40KPa for 2.5h to obtain esterified product A1.

[0092] 2) Adipic acid and 1,4-butanediol were added to the esterification reactor in a molar ratio of 1:1.3 and reacted for 2.5 h at a temperature of 200℃ and a pressure of 40 kPa to obtain esterified product A2;

[0093] 3) Two esters, A1 and A2, are continuously fed into a mixer and mixed. The mixture is reacted at 240℃ and 4KPa for 2.5 hours to obtain a prepolymer. The prepolymer is then further polymerized at 200℃ and 120Pa for 2.5 hours to obtain polyester 1#. The T content is 70mol% and the intrinsic viscosity is 1.39dL / g.

[0094] Polyester 2#: Self-made, the preparation method is basically the same as that of polyester 1#, the difference is that in step 3), the T content is adjusted by adjusting the mass flow rate ratio of A1 and A2, and finally polyester 2# is obtained with a T content of 55 mol% and an intrinsic viscosity of 1.38 dL / g.

[0095] Polyester 3#: Self-made, the preparation method is basically the same as that of polyester 1#, the difference is that in step 3), the T content is adjusted by adjusting the mass flow rate ratio of A1 and A2, and finally polyester 3# is obtained with a T content of 80 mol% and an intrinsic viscosity of 1.37 dL / g.

[0096] Polyester 4#: Self-made, the preparation method is basically the same as that of polyester 1#, the difference is that in step 3), after obtaining the prepolymer, it is continued to polymerize for 3.5h at a temperature of 200℃ and a pressure of 120Pa, and finally polyester 4# is obtained, with a T content of 70mol% and an intrinsic viscosity of 1.50dL / g.

[0097] Polyester 5#: Self-made, the preparation method is basically the same as that of polyester 1#, the difference is that in step 2), adipic acid is replaced with sebacic acid, and finally polyester 5# is obtained, with a T content of 70 mol% and an intrinsic viscosity of 1.38 dL / g.

[0098] Polyester 6#: Self-made, the preparation method is basically the same as that of polyester 1#, the difference is: in step 3), the mass flow ratio of A1 and A2 is adjusted, and finally polyester 6# is obtained, with a T content of 65mol% and an intrinsic viscosity of 1.38dL / g.

[0099] Filler #1: Calcium carbonate, commercially available, D50 particle size is 5μm;

[0100] Filler #2: Calcium carbonate, commercially available, D50 particle size is 10μm;

[0101] Other additives #1: Composed of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio. Both antioxidant 1010 and antioxidant 168 are commercially available.

[0102] Unless otherwise specified, all components (e.g., other additives) used in the parallel examples and comparative examples are the same commercially available products.

[0103] The PBAT composite materials provided in the embodiments and comparative examples of this invention were subjected to performance testing according to the following test methods:

[0104] Film opening grade: PBAT composite material was fed into a conventional blown film machine with a film thickness of 25μm, a production capacity of 50kg / h, and a blown film bag size of 25*(12.5±3.5) to obtain film samples, which were then evaluated.

[0105] K1 The bag opens naturally; a gentle shake will open it completely. K2 The bag can be opened by rubbing it by hand, or by shaking it vigorously. K3 The accordion section cannot be opened naturally; it can be easily torn open. K4 The bag cannot be opened normally, but it can be torn open without deforming. K5 The bag cannot be opened normally; after being torn, the bag is severely deformed.

[0106] Printing performance: Characterized by dyne value. A higher dyne value indicates better ink adhesion, i.e., better printability. Following the order of dyne pen calibration values ​​from smallest to largest, each dyne pen is gently touched perpendicularly to the test surface and then quickly moved across the surface. The maximum calibration value corresponding to the dyne pen that maintains result A is recorded as the dyne value of that sample. Result A indicates that the ink from the dyne pen uniformly and continuously wets the entire surface without forming breaks or stagnation.

[0107] Degradation performance: Biodegradation rate was tested under industrial composting conditions as per standard GB / T 41010-2021.

[0108] The PBAT composite materials of the embodiments and comparative examples of the present invention were prepared by the following preparation method:

[0109] Weigh each component according to the formula, mix them evenly, and then put them into a twin-screw extruder. Extrusion and granulation are carried out at 150-240℃ to obtain PBAT composite material.

[0110] Examples 1-19

[0111] Examples 1-19 provide a series of PBAT composite materials, the formulations of which are shown in Tables 1 and 2.

[0112] Table 1. Formulations (parts by weight) for Examples 1-9

[0113]

[0114] Table 2. Formulations (parts by weight) for Examples 10-19

[0115]

[0116]

[0117] Comparative Examples 1-7

[0118] Comparative Examples 1–7 provide a series of PBAT composite materials, the formulations of which are shown in Table 3.

[0119] Table 3 shows the formulations (parts by weight) for Comparative Examples 1–7.

[0120]

[0121] The properties of the PBAT composite materials in each embodiment and comparative example were determined according to the test methods mentioned above, and the test results are shown in Table 4.

[0122] Table 4. Performance test results of PBAT composite materials in each example and comparative example.

[0123]

[0124]

[0125]

[0126] As can be seen from Table 4:

[0127] The blown film opening grades of the PBAT composite materials in Examples 1 to 19 are all K1 or K2, the dyne values ​​are all above 34, and the degradation performance is all above 80%, indicating that the PBAT composite material of the present invention maintains good degradation performance while taking into account good blown film opening performance and printing performance.

[0128] In Comparative Example 1, the T content of the added PBAT resin was too low, resulting in poor blown film opening performance, low dyne value, and poor printability of the PBAT composite material. In Comparative Example 2, both the polyester and PBAT composite materials had T contents above 52 mol%, leading to poor blown film opening performance and poor degradation performance of the PBAT composite material, failing to meet its conventional application requirements. In Comparative Example 3, no polyester was added, resulting in poor blown film opening performance of the PBAT composite material. In Comparative Example 4, no PBAT resin was added, but instead an equal amount of polyester 1# was used, equivalent to adding PBAT resin with a T content of 70% in Comparative Example 4, resulting in poor printability and degradation performance of the PBAT composite material, failing to meet its conventional application requirements. In Comparative Example 5, PBAT resin 8# was added, resulting in poor blown film opening performance and poor printability of the PBAT composite material. In Comparative Example 6, the amount of polyester was too high, resulting in poor printability and degradation performance of the PBAT composite material, failing to meet its conventional application requirements. In Comparative Example 7, no polylactic acid was added, resulting in poor printability of the PBAT composite material.

[0129] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A PBAT composite material, characterized in that, The components include the following parts by weight: Polylactic acid 3-20 parts, 40-80 parts of PBAT resin Polyester 0.1~10 parts, 10-40 parts of filler; In the PBAT resin, the proportion of terephthalic acid-derived units relative to all dicarboxylic acid-derived units is 44-52 mol%; In the polyester, the dicarboxylic acid derivative unit is derived from terephthalic acid and C. 4~10 The aliphatic dicarboxylic acid, and the terephthalic acid derivative unit accounts for 55~80 mol% of all dicarboxylic acid derivative units, and the diol derivative unit is derived from butanediol; The filler is at least one of calcium carbonate, talc, kaolin, mica powder, or montmorillonite.

2. The PBAT composite material according to claim 1, characterized in that, The melt flow rate of the polylactic acid measured at 2.16 kg and 190 °C was 1~10 g / 10 min.

3. The PBAT composite material according to claim 1, characterized in that, The intrinsic viscosity of the PBAT resin is 0.9 dL / g to 1.5 dL / g.

4. The PBAT composite material according to claim 1, characterized in that, The D50 particle size of the filler is ≤10μm.

5. The PBAT composite material according to claim 1, characterized in that, The PBAT composite material also includes 0.2 to 2 parts of other additives.

6. The PBAT composite material as described in claim 5, characterized in that, The other additives are at least one of stabilizers, antistatic agents, or antifogging agents.

7. The PBAT composite material as described in claim 5, characterized in that, The other additives are antioxidants.

8. The PBAT composite material as described in claim 5, characterized in that, The other additives are UV stabilizers.

9. The PBAT composite material as described in claim 5, characterized in that, The other additives are UV absorbers.

10. The PBAT composite material according to claim 1, characterized in that, The PBAT composite material comprises the following components in parts by weight: 5-15 parts of polylactic acid, 50-70 parts of PBAT resin 2-8 parts polyester 15-35 parts of filler.

11. A method for preparing the PBAT composite material according to any one of claims 1 to 10, characterized in that, The process includes the following steps: mixing the components, melt extrusion, and granulation to obtain the PBAT composite material.

12. The use of the PBAT composite material according to any one of claims 1 to 10 in the preparation of film articles.

Citation Information

Patent Citations

  • Composition containing PBAT (poly(butylene adipate-co-terephthalate)), preparation method thereof and PBAT full biodegradable mulching film

    CN103709687A

  • Polylactic acid-based composite material as well as preparation method and application thereof

    CN116554660A

  • PBAT composite film and preparation method thereof

    CN117089180A